2020
DOI: 10.1590/pboci.2020.120
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Maxillary Canine Impaction in Iraqi Population

Abstract: To investigate the prevalence of maxillary canine impaction and whether the impacted canine cases have had a potentially good or poor prognosis if interceptive treatment was practiced at earlier ages. Material and Methods: 1755 panoramic radiographs of patients, aged 13 to 60 years, attending the University of Babylon, College of Dentistry for the period from November 2016 to July 2018 were collected and assessed for the presence of impacted maxillary canines. Subsequently, four suggested prognostic factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(96 reference statements)
1
1
0
Order By: Relevance
“…However, the British Orthodontic Society -Orthodontic Radiographs guidelines have reported that there is no indication for the routine use of CBCT to detect impacted maxillary canines as the CBCT technique is associated with a higher overall effective dose of ionizing radiation than the conventional radiography. 11 In the present study (Table 1), the female to male ratio was 2.57:1, which is in accordance with many studies which showed that these impactions are more common in females, compared to males, with a ratio of 2:1. 1,3 However, a study conducted by Pico et al found the number of male and female patients in a ratio of 1:1 and justified that by their reduced sample size (only 28 impacted canines in 20 patients).…”
Section: Discussionsupporting
confidence: 92%
“…However, the British Orthodontic Society -Orthodontic Radiographs guidelines have reported that there is no indication for the routine use of CBCT to detect impacted maxillary canines as the CBCT technique is associated with a higher overall effective dose of ionizing radiation than the conventional radiography. 11 In the present study (Table 1), the female to male ratio was 2.57:1, which is in accordance with many studies which showed that these impactions are more common in females, compared to males, with a ratio of 2:1. 1,3 However, a study conducted by Pico et al found the number of male and female patients in a ratio of 1:1 and justified that by their reduced sample size (only 28 impacted canines in 20 patients).…”
Section: Discussionsupporting
confidence: 92%
“…[ 12 ] The prevalence of maxillary canine impaction in (x) population was (6.78%), and in terms of the investigated sample's gender, the number of impacted canines was higher in females than in males and also reported that the impaction occurred more unilaterally than on both sides that agrees with our findings. [ 13 ] The intensity and direction (positive or negative) of a relationship between two variables can be summarized using Spearman's rank correlation coefficient. The answer will always be between 1.0 (a perfect positive correlation) and −1.0 (a perfect negative correlation).…”
Section: Discussionmentioning
confidence: 99%